2006
DOI: 10.1002/cyto.a.20218
|View full text |Cite
|
Sign up to set email alerts
|

Novel apoptosis assay to analyze immunosuppression

Abstract: Background: We developed a novel whole blood assay to assess the effects of immunosuppressants on lymphocyte apoptosis. Methods: Peripheral blood for six experiments for each drug was treated either with cyclosporin A (CsA), mycophenolate acid (MPA), tacrolimus (TRL) or rapamycin (RAPA). Whole blood was stimulated with different concentrations of staurosporine (0-5 lM) for 24 h. Using FACS, apoptosis were measured by Annexin V expression (%cells 6 SEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Nevertheless, our apoptosis assay provided insights into mechanisms of drug monotherapy. Thus, we detected a stronger effect on apoptosis in T cells for MPA compared to SRL or TRL, whereas CsA has no effect [21], confirming a previous study [25]. Evaluating the effects of different drug combinations we showed that overall MPA plus TRL had a greater impact on inhibition of T cell proliferation, and to a lesser extent on T cell surface antigens, than all other drug combinations [13].…”
Section: In Vitro Studiessupporting
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, our apoptosis assay provided insights into mechanisms of drug monotherapy. Thus, we detected a stronger effect on apoptosis in T cells for MPA compared to SRL or TRL, whereas CsA has no effect [21], confirming a previous study [25]. Evaluating the effects of different drug combinations we showed that overall MPA plus TRL had a greater impact on inhibition of T cell proliferation, and to a lesser extent on T cell surface antigens, than all other drug combinations [13].…”
Section: In Vitro Studiessupporting
confidence: 77%
“…Additionally, T helper 1 (TH1) and TH2 cytokines (IL-2, IL-4, IL-6, IL-10, TNF-α und INF-γ) were detected in the serum using multiplex bead array analysis [20]. Apoptotic T cells were quantified using the fluorescent annexin V, and the TUNEL assay was used to detect DNA breaks [21]. The myeloid and plasmocytoid dendritic cell subsets in whole blood were determined without stimulation by specific gating strategies to distinguish these two lineages from leukocytes [22].…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Recent studies have reported that rapamycin impairs viability in several cell types (22,38,39). In this study, it was clearly demonstrated that rapamycin not only affects the differentiation of the porcine NPCCs after transplantation but also suppresses cell expansion.…”
Section: Discussionmentioning
confidence: 73%
“…These instruments have features that can even surpass flow cytometry by minimizing required sample volume by one order of magnitude [50] and increasing the number of simultaneously analyzable parameters per cell [51,52]. Based on increased multiplexing, high-content analysis of cell populations becomes available [53] that would increase our understanding of infection development and may lead to predictive medicine [54][55][56] for preventive therapy [57][58][59]. To date, no flow cytometric marker or set of markers is sensitive and specific enough to allow neonatologists to withhold antibiotic treatment of a sick infant who is suspected to be seriously infected.…”
Section: Discussionmentioning
confidence: 99%